2011
DOI: 10.1007/s00066-011-2262-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiochemotherapy alone to surgery plus radio(chemo)therapy for non-metastatic stage III/IV squamous cell carcinoma of the head and neck

Abstract: Outcomes of radiochemotherapy alone appeared similar to those of surgery plus radio(chemo)therapy. Randomized trials comparing both treatments for different tumor sites are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The 3-year disease-free survival rate was 54% for patients treated with surgery plus RT and 43% for those treated with CCRT (p = 0.425), and no subset analysis of patients with OPC was performed. Rades et al [17] performed a matched-pair analysis in which 148 patients with advanced head and neck squamous cell carcinoma treated with CCRT were matched with 148 patients treated with surgery plus RT, including 134 patients with OPC. Although they reported that the outcomes after treatment with CCRT appeared similar to those after surgery plus RT, no subset analysis of patients with OPC was performed.…”
Section: Discussionmentioning
confidence: 99%
“…The 3-year disease-free survival rate was 54% for patients treated with surgery plus RT and 43% for those treated with CCRT (p = 0.425), and no subset analysis of patients with OPC was performed. Rades et al [17] performed a matched-pair analysis in which 148 patients with advanced head and neck squamous cell carcinoma treated with CCRT were matched with 148 patients treated with surgery plus RT, including 134 patients with OPC. Although they reported that the outcomes after treatment with CCRT appeared similar to those after surgery plus RT, no subset analysis of patients with OPC was performed.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of treatment strategy for laryngeal cancer varies in different oncology centres and depends mainly on the acquired clinical experience as well as on the adopted guidelines regarding therapeutic management in a given centre [1,2,3,4,5,6,7,8,9,10]. The majority of indications for adjuvant radiotherapy are based on the data obtained from microscopic analysis of the surgical specimen [11].…”
Section: Introductionmentioning
confidence: 99%
“…The decision regarding potential adjuvant therapy is also influenced, to some extent, by the type of surgical procedure (partial, total) [12]. Correlations between various clinical and pathological parameters and the risk of recurrence have been described in numerous reports [9,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in the non-surgical management of head and neck squamous cell carcinoma (HNSCC), locoregional failure remains a major cause of morbidity and mortality in this patient population [14,15]. However, early and late side effects limit the overall treatment intensity in unselected cases [11].…”
mentioning
confidence: 99%